Analysis of Effective Broodstock Management and Breeding of Patin Siam (Pangasius hypophthalmus) in BBAT Jambi - Hamid, Mimid A.; W, Wahyu B.; W, Rangga; Lubis, Reni A.; Furusawa, Atomu (Indonesian Society of Scientific Aquaculture (ISSA), 2009)
Aiming to analyze biological character of reproduction and to realize effective breeding activity, annual patin breeding activity 2006 was examined in JFADC Indonesia. Females of two generations, strain of 2001 and 2003 were induced during the year. Various parameters, such as body weight, collected egg weight, number of 1g egg, harvested larvae, were recorded in every trial of breeding. After collecting all of data in 2006, correlation of productivity with fish size and age were analyzed integrating data. All female were also identified by using PIT tag system and alteration of maturity was monitored monthly, observing development of abdomen, from January to June. Accumulated parameters during the year showed negative correlation of egg somatic index (ESI) with fish body weight. Furthermore, hatching rate showed declined tendency as increasing body weight, suggesting less productivity by too-big female. All of elder female performed low productivity due to the low reading of some parameters such as ESI, hatching rate, larvae number/kg. Proportion of matured female was quite high from January until April. Individual monitoring of maturation showed quick reproduction of gonad in 2 month, from January to March, suggesting active reproductive stimulation on this season. Other many females also performed high gonadal maturity and its duration until April in many case. However, maturation has decreased suddenly on May and low maturation had lasted until November. It suppose due to the seasonal alteration of precipitation and remains as awkward issue for stable patin production in Jambi. Keywords: breeding, Asian catfish, egg somatic index, maturation ABSTRAK Evaluasi kegiatan pembenihan patin siam Tahun 2006 di BBAT Jambi Indonesia dilakukan dengan tujuan untuk analisa karakter biologi reproduksi ikan patin siam dan untuk mewujudkan kegiatan pembenihan yang efektif. Betina dari 2 generasi yaitu generasi 2001 dan 2003 dipijahkan selama Tahun 2006. Beberapa parameter seperti bobot tubuh, bobot telur yang diovulasikan (egg somatic index), jumlah 1 gram telur, dan jumlah larva yang dihasilkan dicatat setiap kegiatan pemijahan. Data yang terkumpul dan dianalis, hubungan produktivitas dengan ukuran dan umur induk dievaluasi secara terpadu. Semua betina ditandai dengan menggunakan PIT tag system (micro chip). Perkembangan kematangan gonad dimonitor tiap bulan. Data yang terkumpul menunjukkan adanya korelasi negatif antara egg somatic index dengan bobot tubuh ikan. Selain itu daya tetas cendrung menurun dengan meningkatnya bobot tubuh.. Semua betina yang lebih tua menunjukkan produktivitas yang rendah, hal ini ditunjukkan dengan rendahnya ESI, daya tetas dan jumlah larva/kg induk. Prosentase induk matang gonad cukup tinggi dari bulan Januari sampai April. Pengamatan kematangan gonad per individu menunjukkan siklus reproduksi yang cepat dalam 2 bulan.dari Januari sampai Maret. Beberapa induk lain ditemukan dengan tingkat kematangan gonad yang tinggi pada periode tersebut sampai bulan April. Secara umum tingkat kematangan menurun secara drastis pada bulan Mei dan kematangan yang rendah sampai bulan Nopember. Kata kunci : pembenihan, patin siam, egg somatic index, kematangan